Bio- conversion of the α-linolenic acid (18:3ω3) to long chain -ω3 PUFA’s by detritivore fiddler crab, Uca acuta acuta in the mangrove-estuarine system at Midnapore(East), West Bengal, India - das, Tapas kumar; ghosh, Anita; chakraborty, Susanta kumar (Asian Journal of Biological and Life Sciences, 2015)
The present paper has attempted to highlight the transmission of bio-chemicals especially the omega-3 fatty acids from selected coastal mangrove leaf detritus in the process of foraging activities of Uca acuta acuta, a very common bioenergetically significant mangrove estuarine intertidal fiddler crab ( Brachyura : Ocypodidae ) inhabiting in the coastal belt of Midnapore (East),West Bengal, India and their bio – conversion in vivo .Leaf detritus has been found to contain appreciable amount of –ω3 fatty acids, particularly, the α- linolenic acid (18:3ω3) which is consumed and bio transformed by this studied fiddler crab. On analyzing, the fatty acids from the flesh of the crab species, exhibited considerably higher levels of both 20:5ω.3 (EPA, Ecosapentaenoic acid) and 20:6 ω.3 (DHA, Docosahexaenoic acid) in various tissues of the animal. This intertidal benthic fauna has shown the ability of chain elongation which appeared to be a prerequisite for the de-saturation of the α-linolenic acid (18:3ω3) which in turn produces the essential long chain PUFA’s (Poly Unsaturated Fatty Acids), EPA and DHA.
Keywords: Fiddler Crab; Lipid Bio - Conversion; Mangrove; PUFA’s (EPA and DHA)